Case report: Rare observation of thyroid-like cholangiocarcinoma - Ekaterina Bondarenko; Dmitriy Kalinin; Liliya Urusova; Dariya Pastukhova; Rustam Salimkhanov; Natalia Mokrysheva (Frontiers in Medicine)
Intrahepatic cholangiocarcinoma is a highly malignant tumor with a poor prognosis. Radical surgical resection remains the “gold standard” for improving patient outcomes; however, only a minority of patients qualify for this approach. Intrahepatic cholangiocarcinoma is primarily classified into two major histologic types: small and large ductal cholangiocarcinomas. Nevertheless, rare subtypes with unique diagnostic and prognostic characteristics are increasingly reported. These subtypes often exhibit features such as slow growth, a histologic architecture resembling thyroid tissue, or ductal ectasia, and are associated with a more favorable prognosis. We present the case of a 61-year-old patient with a solitary liver mass initially identified as a hemangioma through imaging studies. Histopathologic examination of the postoperative specimen revealed a thyroid-like structural pattern. Immunohistochemical analysis showed positive staining for CK7 and CK19, confirming the diagnosis of intrahepatic cholangiocarcinoma with a thyroid-like structure. The tumor was completely resected with clear margins, and no evidence of metastasis was found. Consequently, the patient was managed without adjuvant chemotherapy. At 14 months of follow-up, there were no signs of recurrence or metastasis. This clinical case underscores the importance of recognizing novel subtypes of cholangiocarcinoma and exercising vigilance in the management of patients with presumed benign hepatic lesions.